Rizal y la dialéctica, o el diálogo inacabado (Revista de Crítica Literaria Latinoamericana, 2018)
Much debate has been waged over the conundrum of whether the writings of José Rizal project a standpoint of the author with regard to the question of either reform or revolution as the means to effect a decisive change in the political situation of the Philippines in his time. One approach that illuminates the character of this dilemma on the view of Rizal’s writings can be based on the author’s recourse to the method of fiction as a simulacrum of history and as an elaboration of ideologemes in gestation and confrontation. The staging of crossed perspectives in dialectical interaction; that is, in a kind of “dialogism”, sets forth the question of reform or revolution without resolving it once and for all and deferring its resolution indefinitely, such as Mikhail Bahktin conceived the process in his theory of novelistic discourse.
Keywords: Rizal; dialogism; revolution; reform; unfinalizability